Psychological Theorizing as Socioculturally Accurate and Critically Political Transformative Engagement: A Personal Trajectory (with)in-and-(with)out Turkey - Gülerce, Aydan (International Review of Theoretical Psychologies, 2026)
This article reflects on the author’s half-century of scholarship aimed at constructing a transformative psychology. Centering on three decades of participation in the International Society for Theoretical Psychology (ISTP), it offers both a personal theorizing trajectory and a selective retrospective on the Society’s historicity. Building on a transformational model of (post)transdisciplinarity and its (post)metaphysical metatheoretical framework, the work foregrounds sociocultural accuracy and glocally political significance in theoretical psychology. It critiques persistent tendencies toward reductionism, dichotomization, oppositional argumentation, and disciplinary isolation, advocating instead conceptual permeability, dialogical connectivity, and translation across intellectual traditions. Rejecting both unified grand theory and casual eclecticism, the author integrates her psychoanalytic rereadings, Critical social theory, feminist, and postcolonial perspectives. Concepts such as the triopus (a generic self-coordinating system in place of traditional “unit of analysis”) and its dynamic mechanisms of transformational trialectics and transformative triangulation (via objectivation, subjectivation, projectivation) are introduced to counter epistemological fragmentation and ontological closure. Case analyses, including the sociopolitical semiotics of women’s headscarves in Turkey, illustrate the framework’s capacity to address identity politics, oppression, and macro–micro transformations. Ultimately, the article situates theoretical psychology within broader struggles against capitalism, colonialism, authoritarianism, and global brutality, framing scholarly engagement as both intellectual and political praxis.